THE AGE-RELATED FEATURES OF METABOLISM (Innovative Technologica: Methodical Research Journal, 2021)
This article discusses the age-related characteristics of metabolism. The influence of physical exercises on the intensity of oxidative processes, age-related changes in protein, carbohydrate and lipid metabolism and the reasons for a decrease in metabolic intensity.